2018
DOI: 10.1177/0363546518765121
|View full text |Cite
|
Sign up to set email alerts
|

Association Between History of Multiple Concussions and Health Outcomes Among Former College Football Players: 15-Year Follow-up From the NCAA Concussion Study (1999-2001)

Abstract: Associations between a history of multiple concussions and adverse health outcomes were found among former collegiate football players without professional football exposure but were limited to those reporting ≥3 prior concussions. Because only 23.4% of eligible athletes responded to the survey, the possibility of ascertainment bias exists, and our findings should thus be interpreted with some caution. Continued examination within nonprofessional football populations is needed, but findings highlight the need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 42 publications
2
47
1
Order By: Relevance
“…Kerr et al 388 reported a 5.8-fold increased risk of depression after 5–9 concussions in retired professional football players, and Guskiewicz and colleagues389 described a 3-fold increased risk of depression following three or more SRCs among retired football players. Similarly, Kerr et al 390 reported a higher prevalence of moderate/severe depression among former collegiate football players with a history of three or more concussions. Although Fralick and colleagues391 found a twofold higher risk of suicide in individuals who experienced concussion and/or mild traumatic brain injury, this study was not athlete or sport specific, and included the general population.…”
Section: Specific Mental Health Symptoms and Disorders In Elite Athletesmentioning
confidence: 89%
See 1 more Smart Citation
“…Kerr et al 388 reported a 5.8-fold increased risk of depression after 5–9 concussions in retired professional football players, and Guskiewicz and colleagues389 described a 3-fold increased risk of depression following three or more SRCs among retired football players. Similarly, Kerr et al 390 reported a higher prevalence of moderate/severe depression among former collegiate football players with a history of three or more concussions. Although Fralick and colleagues391 found a twofold higher risk of suicide in individuals who experienced concussion and/or mild traumatic brain injury, this study was not athlete or sport specific, and included the general population.…”
Section: Specific Mental Health Symptoms and Disorders In Elite Athletesmentioning
confidence: 89%
“…Undesired and involuntary retirement from sport (eg, because of injury or deselection from sport) is especially associated with an increased risk of mental health symptoms and disorders among transitioning athletes 8 661 664–668. Concussion in sport is associated with subsequent mental health symptoms and disorders among retired elite athletes; however, a causal relationship has not been established 16 390 594 669–672. Other factors associated with adjustment difficulties and mental health symptoms and disorders among former elite athletes include high levels of athletic identity, lack of retirement planning, lower educational attainment, adverse life events, post-sport unemployment and chronic pain 9 18 662 668 673 674…”
Section: Major Stressors and Key Environmental Factors That Influencementioning
confidence: 99%
“…3,4 Over the past decade, the scientific literature has brought increased attention to the risks football players face for sustaining an SRC and the possible development of depression and neurocognitive changes later in life. [5][6][7] This increased focus has been amplified by reports in the lay press that cited examples of significant disablement among football players who sustained SRCs. 8 Beyond the initial restriction from sport, many stakeholders have ongoing concerns regarding short-term and long-term disablement associated with SRCs.…”
mentioning
confidence: 99%
“…F ootball players have one of the highest injury rates at both the collegiate and high school (HS) levels, [1][2][3] likely due to legal contact being allowed during gameplay. Although much of the focus on football injuries has been on concussion 4,5 and other potentially catastrophic conditions, such as cervical spine injuries, [6][7][8] less severe injuries such as cervical muscle strains are not often discussed.…”
mentioning
confidence: 99%